Model Pemberian Remedial Teaching terhadap Hasil Belajar Matematika Siswa Kelas IV SDN 1 Mataram - M. Zainal Mustamiin (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
Learning and instructional are one of the most important elements in supporting student output. In general, if the learning is effective, the results will also be better and vice versa. A student's learning difficulties at school are influenced by internal factors and external factors. The success of the process can be seen from the results of student learning. The purpose of this study was to determine the effectiveness of implementing remedial teaching in mathematics and to determine student completeness after remedial was carried out. The method used in this research is experimental research with the Pre-Experimental Designs approach. This research was conducted in class IV SDN 1 Mataram. The sample in this study was 20 grade IV students at SDN 1 Mataram. The instrument used was the test instrument. The final results of this study obtained t count > t table or 6.65 > 2.09, Ho was rejected and Ha was accepted, meaning that learning mathematics with Remedial Teaching is effective in improving student learning outcomes in mathematics class IV SDN 1 Mataram Academic Year 2022/2023